Effects of micrometer-sized TiB2 on crack mitigation, mechanical and electrochemical performance of a Ni-based alloy fabricated by selective laser melting. (October 2021) - Yang, Shengzhao; Han, Quanquan; Yin, Yingyue; Gao, Jian; Zhang, Zhenhua; Gu, Yuchen; Low, Kenny W.Q.
Highlights: The 2 wt% TiB2 particles addition led to microcrack elimination in enhanced HX. Grain boundaries increased by 31% in enhanced HX due to grain refinement. Enhanced HX exhibited better pitting corrosion resistance than pure HX. Abstract: Hastelloy X (HX) is a nickel-based alloy that is widely used in the aerospace and marine industries. HX alloy is susceptible to hot cracking, however, when it is processed through advanced additive manufacturing technologies such as selective laser melting (SLM) to form complex-shaped components. This study has revealed that microcracking could be mitigated by the addition of 2 wt% microscale TiB2 particles. The results show that the addition of 2 wt% TiB2 contributed to a 31% increase in grain boundaries. The significantly increased grain boundaries enabled uniformity of the residual thermal stress formed during the SLM process, thus leading to the mitigation of cracks. In addition, compared with pure HX, both room-temperature and high-temperature (850 °C) hardness values were noted to improve by 36.8% and 44.5% (respectively) for the TiB2 -reinforced HX. The reinforcement also showed a 44.6% upgrade in ultimate tensile strength compared to the as-fabricated pure HX. The pitting potential of enhanced HX (1.0112 ± 0.0091 V) was found to be higher than that of pure HX (0.95733 ± 0.0117 V), indicating improved pitting corrosion resistance of the as-fabricated enhanced HX, which could be attributable to the grain refinement and increased high angle grain boundaries. The significance of this research is in proposing a novel pathway to mitigate microcracks formed in the SLM of nickel-based superalloy, thus improving both mechanical performance and electrochemical corrosion resistance.